Perancangan Pengendalian Penyebaran Virus Corona di Ruang Kelas Suatu Universitas - Cristofer Javier; I Nyoman Sutapa (Jurnal Titra, 2021)
The purpose of this final project is to design the control of the spread of the corona virus in the classroom. The method used is descriptive research, literature study and extracting protocol information from various literatures. The control design consists of several stages, namely seeking information through literature studies to identify potential points of exposure to COVID-19 in the classroom, identifying causes of failure, identifying the impact or risk of failure. After identifying new problems, an assessment stage is carried out to look for possible impacts or risks so that a control design will be made as a solution. The results show that there are 9 controls that will be designed to control the spread of COVID-19 in classrooms and the final result of this final project produces suggestions for protocol stages according to government standards and universities or schools that have carried out offline learning in the new normal period.